Long-term treatment with lasmiditan in patients with migraine: Results from the open-label extension of the CENTURION randomized trial. (April 2023) - Ashina, Messoud; Roos, Caroline; Li, Lily Qian; Komori, Mika; Ayer, David; Ruff, Dustin; Krege, John Henry
Background: Following the CENTURION phase 3 randomized controlled trial's four-month double-blind phase, this 12-month open-label extension collected data for up to one year about dose optimization, patterns of use, migraine-related disability, and quality of life during lasmiditan treatment. Methods: Migraine patients ≥18 years completing the double-blind phase and treating ≥3 migraine attacks could continue into the 12-month open-label extension. The initial oral lasmiditan dose was 100 mg; the dose could subsequently be adjusted to 50 mg or 200 mg at the investigator's discretion. Results: 477 patients entered and 321 (72.1%) completed the extension; 445 (93.3%) treated ≥1 attack with lasmiditan. Of 11, 327 attacks, 8654 (76.4%) were lasmiditan-treated (84.9% of these involved moderate or severe pain). By study end, 17.8%, 58.7%, and 23.4% of patients were taking lasmiditan 50, 100, and 200 mg, respectively. Mean improvements were observed in disability and quality of life. The most common treatment-emergent adverse event was dizziness (35.7% of patients, 9.5% of attacks). Conclusions: During this 12-month extension, lasmiditan was associated with a high rate of study completion, most attacks were treated with lasmiditan, and patients reported improvements in migraine-related disability and quality of life. No new safety findings were observed with longer exposure. Trial registration: ClinicalTrials.gov (NCT03670810); European Union Drug Regulating Authorities Clinical Trials Database (EUDRA CT: 2018-001661-17).